A Study of Sexual Behavior, Sex Information and Self-Concept in Adolescent Venereal Disease Patients - Allen, Joan (1965)
A Research Report Presented to the Faculty of the Raymond A. Kent School of Social Work, University of Louisville, in partial fulfillment of the requirements for the degree of Master of Science in Social Work by Joan Allen, Ralph H. Childers, Hubert Crawford, Olin Gentry, Jr., Ralph Hollon, Carol Hill and Evelyn J. McKissick in June of 1965